2011
DOI: 10.1262/jrd.10-136t
|View full text |Cite
|
Sign up to set email alerts
|

Basal Levels and GnRH-induced Responses of Peripheral Testosterone and Estrogen in Holstein Bulls with Poor Semen Quality

Abstract: Abstract. The present study investigated the basal levels and GnRH-induced responses of peripheral testosterone and estrogen in Holstein bulls with poor semen quality. On the basis of semen parameters, bulls (n=5) having poor semen quality were selected as experimental bulls, and good semen quality bulls (n=4) were used as control bulls. Both groups were treated intramuscularly once with GnRH (250 μg of fertirelin acetate). Blood samples were collected at -1 day (d),-30 min and 0 h (treatment) followed by ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…Each bull, irrespective of their semen quality, showed different levels, pattern of LH release and time taken to attain peak values, which was in accordance with a similar study carried out on HF bulls (Devkota et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Each bull, irrespective of their semen quality, showed different levels, pattern of LH release and time taken to attain peak values, which was in accordance with a similar study carried out on HF bulls (Devkota et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…By contrast, Post et al (1987b) and Devkota et al (2011) observed a positive relationship between the fertility or semen parameters and the hormonal response to GnRH. Therefore, the present study was designed with the objective of investigating whether a difference existed in gonadal and pituitary hormonal response to exogenous GnRH challenge in crossbred bulls with differing semen quality.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Importantly, although steroid production by the testis is basal at birth, serum concentrations of estradiol in the bull calf begin to increase soon thereafter, and serum concentrations of testosterone increase from around 10 weeks of age [41,42]. In the mature bull, GnRHinduced increases in circulating testosterone and both basal and GnRH-induced increases in circulating estradiol are reported to be lower in bulls with poor semen quality [43].…”
Section: Discussionmentioning
confidence: 99%
“…Bull fertility is an important aspect because one bull may serve around 20 females under natural conditions or hundreds of thousands under an artificial insemination program (Devkota et al, 2011). Reliable fertility information can be obtained on several bulls by using them to impregnate a large number of cows or by evaluating their semen quality.…”
Section: Introductionmentioning
confidence: 99%